A regularized trace of an even-order differential operator with bounded operator coefficient given in a finite interval - Akgun, Fatma Aydin; Bayramoglu, Mamed (UNIV NIS, FAC SCI MATH, 2023)
In this study, we obtain a regularized trace formula of an even-order differential operator with a bounded operator coefficient given in a finite interval.
Keywords: Regularized trace; Operator coefficient; Differential operator; EIGENVALUE; Mathematics